Engineering a 3D wounded skin equivalent to study early inflammatory and regenerative responses in vitro - Nuwayhid, Rima; Ngoc-Huyen, Nguyen; Notov, Dmitry; Langer, Stefan; Kurow, Olga (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTraditional models for studying wound healing, including 2D cell cultures and animal models, present substantial limitations in mimicking human skin physiology. In this study, we present a three-dimensional wounded skin equivalent (3DWoundSE) composed of human cells as a physiologically relevant in vitro platform to investigate wound healing processes.MethodsThe model builds upon a previously established 3D skin equivalent (3DSE) and incorporates a reproducible partial-thickness dermal punch wound. We characterised the 3DWoundSE using histology, cytotoxicity assays, immunofluorescence staining, and pro-inflammatory cytokine profiling at multiple time points post-wounding.ResultsResults revealed hallmark wound responses, including increased lactate dehydrogenase (LDH) and apoptosis-inducing factor (AIF) expression, dynamic Ki-67 proliferation changes, and a pro-inflammatory cytokine response, notably elevated IL-6, IL-8, IL-33 and TNF-α levels.DiscussionCompared to the intact 3DSE, this 3DWoundSE demonstrated enhanced responsiveness to injury and cytotoxic stimuli, confirming its utility for early wound response assessment. This platform offers a reproducible and ethically sound alternative to animal models, with potential applications in dermatological research, drug development, and therapeutic screening.